The Performance of Carbon Fibre Composites as ICCP Anodes for Reinforced Concrete Structures. (20th December 2012) - Van Nguyen, Chinh; Lambert, Paul; Mangat, Pal; O'Flaherty, Fin; Jones, Graeme
Abstract : Cathodic protection has been proven to be one of the most widely applicable and cost-effective solutions for tackling steel corrosion in reinforced concrete. In this study, the possible use of carbon fibre composites, which are primarily used to strengthen concrete members, has been investigated as impressed current cathodic protection anodes. Carbon fibre anodes have been assessed in both concrete and calcium hydroxide solution. Two bonding mediums incorporating epoxy and geopolymer have also been investigated. The results demonstrate that epoxy resin can be used for bonding carbon fibre fabric anodes to reinforced concrete structures while geopolymer is more effective for bonding carbon fibre reinforced polymer (CFRP) rod into preformed grooves in the concrete surface. The dissolution of carbon fibre anode appears to stablise after a period of time, dependent upon the size and shape of the anode and applied voltage and current. Based on the present results, a maximum current density of 128 mA/m 2 of reinforcing steel area is recommended for the operation of CFRP fabric anode and 64 mA/m 2 of reinforcing steel area for that of CFRP rod anode.